PENGEMBANGAN BAHAN AJAR ILMU PENGETAHUAN ALAM PROJECT BASED LEARNING DI SEKOLAH DASAR NEGERI PONTIANAK - Muri, Lidia; Marzuki, Marzuki; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: The aims of this research is to produce natural science materials based on project based learning. The Research method is research development, the model is Dick and Carey with technique of analyze data used is descriptive percentage and calculate average.Data collection was done by questionnaires obtained with expert validation and questionnaires from teachers and learners. Data from questionnaires of expert validation is 79.17% and teachers is 97.22%, the average is 8.82 with good category. The questionnaire response from the teacher obtained 85.33% with good category. Positive responses from questionnaire learners obtained 82.65% with good category. The result of learners data test obtained 92,17% with good category. The result product is a manual. Â Key words: Developing, , Project based learning model.